Body Shaming Act as a Crime in Indonesian Criminal Law - Erdianti, Ratri Novita; Wasis, Wasis; Samira, Echaib; Al-Fatih, Sholahuddin (Universitas Muhammadiyah Surabaya, 2022)
Body shaming is an act that often occurs in society. Body shaming is an act that refers to the activity of criticizing and commenting negatively on the physical or other person's body or the act of mocking / insulting a person's body shape or body size or someone's appearance. Often this body shaming is carried out only for jokes or jokes among the public, but basically if viewed from a criminal law perspective, basically this body shaming meets the criteria for a criminal offense in the defamation article regulated in the Criminal Code. criminal offense in contempt which can be punished by using article 315. Considering the legal rules regarding body shaming in the Criminal Code and outside the Criminal Code which in the regulation do not mention directly about body shaming, it is necessary to review the rules governing body shaming so that it does not give rise to multiple interpretations. The formulation of the problem in this study is the regulation of criminal acts in insulting body image (body shaming) in terms of the Criminal Code and Legislation Outside the Criminal Code. The method used in this article uses a normative juridical research method. Later this study will review the legal construction of the law on body shaming in criminal law in Indonesia. In the regulation of the Criminal Code, body shaming is regulated in the elements of a criminal act, article 315. In addition, Indonesia already has a number of rules that regulate behavior on the internet, such as Law No. 11 of 2008 concerning Electronic Information and Transactions, which was later amended in Law No. 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Transactions. Electronic (UU ITE)